Strategies for the Treatment of Anxious Depression - Sinclair, Heather Q. (MD Conference Express, 2009)
Major depression is one of the most treatable medical illnesses. There is a strong correlation between anxiety symptoms and low rates of remission in patients with major depressive disorder (MDD) [Davidson JR, et al. Depress Anxiety 2002; Silverstone PH et al. Int Clin Psychopharmacol 2002]. This article discusses the role of anxiety in patients with major depressive disorder at the APA annual meeting.